Investigation of the Enhancement Effect of Heat Transfer Using Micro Channel. (August 2015) - Xia, Liang; Chan, Yue
Abstract: This paper reports an investigation of the enhanced heat transfer effect in micro sized channels. In particular, a simulation model has been established using computational fluid dynamics (CFD) platform, i.e., Fluent to investigate such micro effect. Here, hot fluid flow is squeezed into the micro channel and the heat is gradually transferred into the cold surface boundaries, i.e., top and bottom surfaces of the channel having rectangular cross-sections. The area of inlet is varied to investigate and identify the enhanced heat absorption arising from the size effect and it is found that heat transfer rate per unit effective heat transfer area is greater if the inlet area becomes smaller. Lower pressure drop can also be deduced if smaller radii channels are considered. Least but not last, a new design of heat exchanger is proposed based on these extra micro-effects.